Development of a coffee lexicon and determination of differences among brewing methods - Sanchez Alan, Karolina (Kansas State University, 2015)
A total of more than 100 different coffee samples from 14 countries around the world were used to create a coffee lexicon. The first list of terms consisted of 74 attributes that were developed from the review of 13 samples from Colombia. A second development incorporated an existing commercial lexicon and examined an additional of 72 coffee samples from different parts of the world. Validation sessions were also performed with 20 samples from the area of San Adolfo, Colombia. Principal Component Analysis (PCA) was used to mapped the scores obtained during the validation phase of the terminology, the panelists were able to described specific characteristics that were present in the coffee samples such as sweet, nutty and fruity notes, as well as the differentiation of notes such as burnt, smoky, astringent, acrid and bitter. At the end of the process, a total of 110 attributes and their references were identified. Another study was conducted to identify the sensory properties of three coffee samples using four different brewing methods. The coffee samples were prepared using a consumer drip coffee maker, a home or food service automated espresso machine, a coffee grader “cupping” method and a filtered infusion method. The cupping method produced a higher intensity for the “roasted” flavor attribute across all samples. This method also tended to produce higher scores for burnt and acrid than other brewing methods. Flavor and aroma attributes both varied with preparation methods, but not necessarily in the same ways. The drip brewing method showed the most differences in the three coffee samples for aroma, flavor and aftertaste attributes, but other methods may be appropriate depending on the objectives of each study.
Keywords: Coffee; Lexicon; Brewing MethodsSensory; Food Science (0359)